Chinese Cerebrovascular Neurosurgery Society and Chinese Interventional & Hybrid Operation Society, of Chinese Stroke Association Clinical Practice Guidelines for Management of Brain Arteriovenous Malformations in Eloquent Areas - Wang, Mingze; Jiao, Yuming; Zeng, Chaofan; Zhang, Chaoqi; He, Qiheng; Yang, Yi; Tu, Wenjun; Qiu, Hancheng; Shi, Huaizhang; Zhang, Dong; Kang, Dezhi; Wang, Shuo; et al. (Frontiers in Neurology, 2021)
Aim The aim of this guideline is to present current and comprehensive recommendations for the management of brain arteriovenous malformations (bAVMs) located in eloquent areas. Methods An extended literature search on MEDLINE was performed between Jan 1970 and May 2020. Eloquence-related literatures were further screened and interpreted in different subcategories of this guideline. The writing group discussed narrative text and recommendations through group meetings and online video conferences. Recommendations followed the Applying Classification of Recommendations and Level of Evidence proposed by American Heart Association/ American Stroke Association. Prerelease review of the draft guideline was performed by 4 expert peer reviewers and by the members of Chinese Stroke Association. Results In total, 809 out of 2493 literatures were identified to be related to eloquent structure or neurological functions of bAVMs. Three-hundred and forty-eight literatures were comprehensively interpreted and cited by this guideline. (Fig.1) Evidence-based guidelines were presented for the clinical evaluation and treatment of bAVMs with eloquence involved. Topics focused on neuroanatomy of activated eloquent structure, functional neuroimaging, neurological assessment, indication and recommendations of different therapeutic managements. Fifty-nine recommendations were summarized, including 20 in Class I, 30 in Class IIa, 9 in Class IIb and 2 in Class III. Conclusions The management of eloquent bAVMs remains challenging. With the evolutionary understanding of eloquent areas, the guideline highlights the assessment of eloquent bAVMs, and strategy for decision making in the management of eloquent bAVMs.